Usaha Makanan Sehat “Onebiteroll” Bogor dan Strategi Pengembangannya - Dita Amanah; Fatin Nadhira; Dedy Ansari Harahap (Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
This journal was created with the aim of observing an online food business in Bogor called Onebiteroll, which sells healthy food in the form of vegetable spring rolls from Vietnam. The business is interesting and has great potential in the future but has several problems that make this business run ineffective and consistent, some of which are lack of capital, less than optimal promotions, amateur product photos, and packaging that is not environmentally friendly. Observing the running of the business and making a questionnaire and asking the owners and employees of this business is a method of collecting data for this research. The solution that has been given is to use the hookle application to help make promotions more consistent, optimize product photos and replace packaging to make it more environmentally friendly, such as packaging made from paper.